THE ROLE OF GREEN MARKETING COMMUNICATION IN CONSUMERS’ GREEN PURCHASE BEHAVIOUR - Alwi, Muhamad Yusup; Pratomo, Luki Adiati (Jurnal Ekonomi Trisakti, 2025)
This study investigates how customer purchasing behavior is affected by green marketing communications.  A quantitative approach was used, and 200 participants completed an online survey to collect data.  The data was interpreted using statistical techniques, such as structural equation modeling, hypothesis evaluations, and reliability and validity tests.  According to the study, consumer attitudes have a major influence on how attentive consumers are to environmental marketing, and there is a strong correlation between green marketing communication and consumer purchase decisions.  Gender and educational attainment, however, have no discernible effects on green marketing messaging, according to the study.  According to the findings, companies who sell sustainable goods ought to concentrate on enhancing their green marketing initiatives and cultivating favorable customer perceptions of environmental responsibility. However, this study has some drawbacks, namely its reliance on online data collecting and convenience sampling, which may limit how broadly the findings can be applied.  Additional demographic and psychological variables that might affect the relationship between green marketing messaging and customer behavior should be investigated in future research.  The study's conclusions offer insightful suggestions for businesses and legislators looking to improve sustainable consumer practices through successful marketing campaigns.